Strategy Model for Increasing the Potential of Zakat through the Crowdfunding-Zakat System to overcome Poverty in Indonesia - Ajeng Sonial Manara; Arif Rachman Eka Permata; R. Gatot Heru Pranjoto (International Journal of Zakat, 2018)
Indonesia, through Presidential Regulation No. 18 of 2007, Indonesia's annual economic development goals are directed to encourage economic growth in order to expand employment and reduce poverty. With implications for income equity, zakat has a strategic potential that is feasible to be developed into one of the instruments of income distribution in Indonesia. Based on data collection and distribution of funds of the Zakat Management Organization below, in 2015, the total fund collection experienced a growth of 10.62% compared to 2014. This study will discuss discussing the related Strategy Model for Increasing the Potential of Zakat through Crowdfunding-Zakat System for poverty alleviation in Indonesia. Abdullah (2015) in his research developed a new methodology to measure poverty alleviation in Pakistan, focusing on consumption / expenditure of poor households for basic needs, government expenditure in terms of zakat and the number of recipients of zakat as the three main determinants. In Syafiq (2014) the realization of the prospect of zakat in the modern economy must also be supported by the management of zakat management organizations in a modern way, meaning that in the fundraising strategy, and the distribution must follow modern management and strategy as a company in achieving its target. Thaker and Pitchay (2018) through their research revealed that crowdfunding model is used to raise funds to develop Waqf land in Malaysia where in their research they propose a sustainable model that can overcome liquidity problems faced by Waqf institutions in developing Waqf land. Using qualitative research methods with a literature study approach. With the crowdfinding-zakat system, it provides convenience in the collection of zakat funds from the wider community in line with several regions in Indonesia that show the potential and positive impact on income distribution.